MATHEMATICAL MODELLING OF LASER-ASSISTED LIPOLYSIS - D. V. Kudrytski; S. V. Shakhrai; Yu. M. Gain (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of mathematical modeling of laser-assisted lipolysis procedure using a medical laser with a wavelength of 970 nm and 1,560 nm are compared with experimental data obtained as a result of surgical treatment of 12 patients.